An experimental and computational study to resolve the composition of dolomitic lime. Issue 19 (8th February 2016) - Grant, J.; Pesce, G. L.; Ball, R. J.; Molinari, M.; Parker, S. C.
Abstract : Dolomite phase separates during calcination suggesting enhanced properties of its mortars might be artificially produced by mixing fine powdered hydroxides. Abstract : Lowering the environmental impact, and moving away from a reliance on cement based binders, is a key challenge of the construction industry. Dolomitic lime binders are produced at lower temperatures than cement, re-adsorb released CO2 during strengthening, and are recognised for their superior permeability, flexibility and resilience. While dolomite consists of alternating layers of magnesium and calcium the distribution in dolomitic lime is not yet fully understood. Here we combine experimental and computational methods to confirm that dolomite phase separates into lime and periclase during thermal decomposition. Raman inactivity of decomposed dolomite agrees with XRD studies suggesting phase separation. Our results rule out the formation of mixed phase oxides and predict an upper bound for bulk and surface substitution defect concentrations. Transferred to study macroscopic models of lime mortars these findings indicate that only the pure phases need be considered and that for the construction industry superior artificial mortars should be obtained from mixing fine powders of pure magnesium and calcium hydroxide.